Preparation method and application of gypsum-based silica gel honeycomb type composite photocatalytic plate

Through the combination of gypsum and silica sol and the impregnation preparation method of titanium dioxide photocatalyst, the existing photocatalytic material support has high cost, complex process and poor compatibility, and the efficient and low-cost photocatalytic degradation effect is achieved.

CN119608136APending Publication Date: 2025-03-14CHINA UNIV OF GEOSCIENCES (BEIJING) +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411496961.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The support of existing photocatalytic materials has high cost, complex preparation process, serious slag loss problems, and the compatibility between the support and the photocatalyst is not good enough, resulting in low photocatalytic degradation efficiency and high price.

Method used

Using gypsum as a matrix, a gypsum-based silicone gel honeycomb composite photocatalytic plate was prepared by combining with a silica sol and a titanium dioxide photocatalyst. The method includes mixing gypsum and silica sol, forming, then immersing the titanium dioxide photocatalyst, and finally drying to make a photocatalytic plate.

Benefits of technology

It has achieved photocatalytic materials with excellent mechanical properties, high catalytic efficiency and good compatibility. The photocatalytic degradation efficiency of 24 hours is more than 75%, and it has simple process, low energy consumption, low cost, and easy industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608136A_ABST
    Figure CN119608136A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a gypsum-based silica gel honeycomb type composite photocatalytic plate. The preparation method comprises the following steps: S1, preparing a gypsum-based honeycomb carrier based on gypsum and silica sol; s2, preparing titanium dioxide photocatalytic slurry; s3, preparing titanium dioxide photocatalytic slurry containing silica sol; s4, preparing the gypsum / silica gel honeycomb type composite photocatalytic plate, providing the gypsum / silica gel honeycomb type composite photocatalytic plate which is excellent in mechanical property, high in specific surface area, good in compatibility and high in photocatalytic degradation efficiency, and the 24-hour photocatalytic degradation efficiency reaches 75% or above. The invention further discloses application of the preparation method of the gypsum-based silica gel honeycomb type composite photocatalytic plate in photocatalytic reaction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photocatalysis technology, and more specifically, to a preparation method of a gypsum-based silicone gel honeycomb composite photocatalytic plate and application thereof. Background Art

[0002] In recent years, with the progress of science and technology and the improvement of people's living standards, atmospheric pollution has become more and more serious. Organic pollutants such as formaldehyde and toluene that are prevalent in buildings seriously affect people's lives and health. Titanium dioxide has the advantages of high efficiency and low cost in air pollution control, but it requires a carrier with high specific surface area, high porosity, corrosion resistance and other characteristics to carry titanium dioxide, and then prepare a good catalytic product. In the market, photocatalytic purification technology has been combined with traditional decorative materials such as coatings, wallpapers, and lamps, and some new purification functional materials have been developed. However, on the one hand, due to the complexity of the preparation process and the high cost of the carrier, its price is relatively high. On the other hand, due to the poor compatibility between the carrier and the photocatalyst, the photocatalytic product falls off. Therefore, it is inevitable to prepare photocatalytic products with high degradation efficiency, low price, and good compatibility between the photocatalyst and the carrier.

[0003] In the prior art, catalyst carriers are mostly foam ceramics, honeycomb ceramics, etc., which have the disadvantages of high energy consumption, complex preparation process, and slag falling, which limits the application of catalysts. Gypsum has a certain hardness after hydration. Under the microscopic view, the hardened gypsum is mostly fibrous accumulation with many pores. The properties of gypsum make it possible to use it as a carrier to prepare photocatalytic materials. However, the thickness of the gypsum carrier will seriously affect the performance of the catalyst, and products that are too thin have the disadvantages of insufficient strength, slag falling, and easy damage to the product. Silica sol is an aqueous solution of nano-silicon dioxide, which can form a colorless, transparent, strong, and rich pore structure silica gel after dehydration and drying.

[0004] Therefore, it is very meaningful to use gypsum as the matrix, load silica sol on the surface to enrich the pore structure, and finally load titanium dioxide photocatalyst to prepare a photocatalytic material with excellent mechanical properties, high catalytic efficiency and good compatibility. Summary of the invention

[0005] In order to solve the technical defects and deficiencies in the prior art, the present invention provides the following technical solutions: a preparation method of a gypsum-based silicone gel honeycomb composite photocatalytic plate and its application, providing a gypsum / silicone gel honeycomb composite photocatalytic plate with excellent mechanical properties, high specific surface area, good compatibility and high photocatalytic degradation efficiency, and the 24h photocatalytic degradation efficiency is more than 75%.

[0006] In one aspect, the present invention provides a method for preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate, comprising the following steps:

[0007] S1, preparation of gypsum-based honeycomb carrier based on gypsum and silica sol;

[0008] S2, preparing titanium dioxide photocatalytic slurry;

[0009] S3, preparing titanium dioxide photocatalytic slurry containing silica sol;

[0010] S4, preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate.

[0011] Preferably, the S1 comprises:

[0012] S11, mixing gypsum, silica sol and water to obtain a first mixture;

[0013] S12, stirring the first mixture with a stirrer to obtain a mixed slurry.

[0014] S13, after stirring evenly, injecting the mixed slurry into a honeycomb mold, and molding, demoulding, and drying after 30 minutes to obtain a gypsum-based honeycomb carrier.

[0015] Preferably, the concentration of the silica sol is 30% to 50%, the stirring speed is 100 to 500 r / min; the stirring time is 1 to 5 min; the stirring temperature is 15°C to 35°C; the mass ratio of gypsum: silica sol: water is 100:(1-3):(30 to 40).

[0016] Preferably, S2 includes:

[0017] S21, mixing the nano titanium dioxide photocatalyst and water to obtain a first mixture;

[0018] S22, stirring the first mixture to obtain titanium dioxide photocatalytic slurry.

[0019] Preferably, the stirring speed is 300 r / min to 1000 r / min, the stirring time is 1 to 5 min, the stirring temperature is 15° C. to 35° C., and the solid content of the titanium dioxide photocatalytic slurry is 10% to 30%.

[0020] Preferably, S3 includes:

[0021] S31, mixing the titanium dioxide photocatalytic slurry and silica sol to obtain a second mixture; wherein the mass ratio of the titanium dioxide photocatalytic slurry: silica sol = (10-100): 100;

[0022] S32, stirring the second mixture to obtain titanium dioxide photocatalytic slurry containing silica sol.

[0023] Preferably, in the titanium dioxide photocatalytic slurry containing silica sol, the concentration of silica sol is 30% to 50%, the stirring speed is 100 r / min to 300 r / min, the stirring time is 1 to 5 min, and the stirring temperature is 15°C to 35°C.

[0024] Preferably, S4 includes:

[0025] S41, using a fixture to immerse the gypsum-based honeycomb carrier into the titanium dioxide photocatalytic slurry containing silica sol for impregnation, to obtain a gypsum-based silica sol honeycomb composite photocatalytic plate with a titanium dioxide photocatalyst loaded on the surface;

[0026] S42, placing the gypsum-based silica sol honeycomb composite photocatalytic plate with titanium dioxide photocatalyst loaded on the surface in an oven for drying, and obtaining the gypsum-based silica gel honeycomb composite photocatalytic plate after drying.

[0027] Preferably, the immersion temperature is 15°C to 35°C, and the immersion time is 5s to 60s; the drying temperature is 50°C to 80°C, and the drying time is 3h to 12h.

[0028] The second aspect of the present invention is to provide the application of the preparation method of the gypsum-based silicone gel honeycomb composite photocatalytic plate of the first aspect in a photocatalytic reaction.

[0029] Beneficial effects of the present invention:

[0030] (1) First, gypsum is used as a carrier by utilizing its hydration and hardening properties. At the same time, a small amount of silica sol will form a porous structure inside the carrier after drying. Then, after the gypsum honeycomb carrier is immersed in a titanium dioxide photocatalytic slurry containing silica sol, the silica sol can play a bonding role, allowing the photocatalyst to adhere to the surface of the carrier. Finally, a gypsum-based silica gel honeycomb composite photocatalytic plate with excellent mechanical properties, high catalytic efficiency and good compatibility is obtained. It has the advantages of simple process, low energy consumption, low cost and easy industrialization.

[0031] (2) The preparation method has a simple process flow, excellent photocatalytic performance prepared by impregnation, and low production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is a flow chart of the method for preparing the gypsum-based silicone gel honeycomb composite photocatalytic plate provided by the present invention.

[0033] Figure 2 The flowchart of step S1 provided by the present invention.

[0034] Figure 3 This is a flow chart of step S2 provided by the present invention.

[0035] Figure 4 The flowchart of step S3 provided by the present invention.

[0036] Figure 5 The flowchart of step S4 provided by the present invention. DETAILED DESCRIPTION

[0037] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0038] like Figure 1-5 As shown, the first aspect of this embodiment provides a method for preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate, comprising the following steps:

[0039] S1, preparation of gypsum-based honeycomb carrier based on gypsum and silica sol;

[0040] As a preferred embodiment, the S1 includes:

[0041] S11, mixing gypsum, silica sol (source: Dezhou Jinghuo Technology Glass Co., Ltd., main component: SiO2·nH2O, the same below) and water to obtain a first mixture;

[0042] When silica sol is used in the gypsum carrier, a small amount of silica sol will form a porous structure inside the carrier after drying, and excessive use will affect the strength of the carrier.

[0043] S12, stirring the first mixture with a stirrer to obtain a mixed slurry.

[0044] As a preferred embodiment, the concentration of the silica sol is 30% to 50%, and the stirring speed is 100 to 500 r / min; if the stirring time is too long, the gypsum will harden directly, so the stirring time is 1 to 5 minutes; the stirring temperature is 15°C to 35°C.

[0045] As a more preferred embodiment, the concentration of the silica sol is 35% to 40%, the stirring speed is 200 to 300 r / min, the stirring time is 2 to 3 min, and the stirring temperature is 20°C to 30°C.

[0046] S13, after stirring evenly, injecting the mixed slurry into a honeycomb mold, and molding, demoulding, and drying after 30 minutes to obtain a gypsum-based honeycomb carrier.

[0047] As a preferred embodiment, the mass ratio of gypsum: silica sol: water is 100: (1-3): (30-40).

[0048] As a more preferred embodiment, the mass ratio of gypsum: silica sol: water is =100:(2-2.5):(30-35).

[0049] S2, preparing titanium dioxide photocatalytic slurry;

[0050] As a preferred embodiment, S2 includes:

[0051] S21, mixing the nano titanium dioxide photocatalyst and water to obtain a first mixture;

[0052] S22, stirring the first mixture to obtain titanium dioxide photocatalytic slurry.

[0053] As a preferred embodiment, the stirring speed is 300 r / min to 1000 r / min, the stirring time is 1 to 5 min, the stirring temperature is 15° C. to 35° C., and the solid content of the titanium dioxide photocatalytic slurry is 10% to 30%.

[0054] As a more preferred embodiment, the stirring speed is 500-700 r / min, the stirring time is 2-3 min, the stirring temperature is 20° C.-30° C., and the solid content of the titanium dioxide photocatalytic slurry is 15-20%.

[0055] S3, preparing titanium dioxide photocatalytic slurry containing silica sol;

[0056] As a preferred implementation, S3 includes:

[0057] S31, mixing the titanium dioxide photocatalytic slurry and silica sol to obtain a second mixture; wherein, the mass ratio of the titanium dioxide photocatalytic slurry: silica sol = (10-100): 100; in the slurry, the silica sol can play a bonding role, so that the photocatalyst is attached to the surface of the carrier, but the strength of the low-concentration silica sol after drying is not high enough, the photocatalyst is not firmly bonded, and the high-concentration silica sol has insufficient bonding channels, which affects the photocatalytic efficiency. Therefore, as a more preferred embodiment, the mass ratio of the titanium dioxide photocatalytic slurry: silica sol = 30-50:100.

[0058] S32, stirring the second mixture to obtain titanium dioxide photocatalytic slurry containing silica sol.

[0059] As a preferred embodiment, in the titanium dioxide photocatalytic slurry containing silica sol, the concentration of silica sol is 30% to 50%, the stirring speed is 100 r / min to 300 r / min, the stirring time is 1 to 5 min, and the stirring temperature is 15°C to 35°C.

[0060] As a more preferred embodiment, in the titanium dioxide photocatalytic slurry containing silica sol, the concentration of silica sol is 35% to 40%, the stirring speed is 200 r / min, the stirring time is 2 min, and the stirring temperature is 20°C to 25°C.

[0061] S4, preparing a gypsum-based silica gel honeycomb composite photocatalytic plate;

[0062] As a preferred implementation, S4 includes:

[0063] S41, using a fixture to immerse the gypsum-based honeycomb carrier into the titanium dioxide photocatalytic slurry containing silica sol for impregnation, to obtain a gypsum-based silica sol honeycomb composite photocatalytic plate with a titanium dioxide photocatalyst loaded on the surface;

[0064] As a preferred embodiment, the immersion temperature is 15°C to 35°C, and the immersion time is 5s to 60s, because a short immersion time results in less catalyst loaded on the surface and low catalytic efficiency, while a long immersion time results in too thick silica sol on the surface and low catalytic efficiency.

[0065] As a more preferred embodiment, the immersion temperature is 20°C to 30°C, and the immersion time is 15s to 20s.

[0066] S42, placing the gypsum-based silica sol honeycomb composite photocatalytic plate with titanium dioxide photocatalyst loaded on the surface in an oven for drying, and obtaining the gypsum-based silica gel honeycomb composite photocatalytic plate after drying.

[0067] As a preferred embodiment, since the drying time is too short and the photocatalyst is not dried, and too long will damage the photocatalyst; the temperature is too high and the photocatalyst is also damaged, the drying temperature is 50℃~80℃, and the drying time is 3h~12h.

[0068] As a more preferred embodiment, the drying temperature is 60° C. to 65° C., and the drying time is 4 h to 5 h.

[0069] The second aspect of this embodiment is to provide the application of the preparation method of the gypsum-based silicone gel honeycomb composite photocatalytic plate of the first aspect in photocatalytic reaction.

[0070] Application Examples

[0071] Example 1

[0072] This embodiment provides a method for preparing a photocatalytic plate, comprising the following steps:

[0073] 1) Mix gypsum, silica sol and water, and stir them with a stirrer to obtain a mixed slurry. The silica sol concentration is 30%, the stirring speed is 100r / min, the stirring time is 5min, and the stirring temperature is 15°C. The ratio is gypsum: silica sol: water = 100:1:30. After stirring evenly, the mixed slurry is injected into the honeycomb mold, and after 30 minutes, it is molded, demolded, and dried to obtain a gypsum-based honeycomb carrier.

[0074] 2) Mixing the nano-titanium dioxide photocatalyst and water to obtain a titanium dioxide photocatalytic slurry with stirring at a stirring speed of 300 r / min, a stirring time of 5 min, a stirring temperature of 15° C., and a solid content of the titanium dioxide photocatalytic slurry of 10%.

[0075] 3) Mixing and stirring the titanium dioxide photocatalytic slurry and silica sol to obtain a titanium dioxide photocatalytic slurry containing silica sol. The silica sol concentration is 30%, the stirring speed is 100 r / min, the stirring time is 1 min, and the stirring temperature is 15°C.

[0076] Ratio: titanium dioxide photocatalytic slurry: silica sol = 10:100

[0077] 4) Immerse the gypsum-based honeycomb ceramic carrier in 1) into the titanium dioxide photocatalytic slurry containing silica sol in 3) to obtain a gypsum / silica sol honeycomb composite photocatalytic plate with a surface loaded titanium dioxide photocatalyst. The gypsum-based silica sol honeycomb composite photocatalytic plate with a surface loaded titanium dioxide photocatalyst is placed in an oven for drying, and a gypsum-based silica gel honeycomb composite photocatalytic plate is obtained after drying. The immersion temperature is 35°C, the immersion time is 5s, the drying temperature is 50°C, and the drying time is 12h. This embodiment can obtain a gypsum-based silica gel honeycomb composite photocatalytic plate with a 24h photocatalytic efficiency of 78%. The titanium dioxide content is 3.1%

[0078] Comparative Example 1

[0079] This comparative example provides a method for preparing a photocatalytic plate, comprising the following steps:

[0080] 1) Mix gypsum, silica sol and water, and stir them with a stirrer to obtain a mixed slurry. The silica sol concentration is 30%, the stirring speed is 100r / min, the stirring time is 5min, and the stirring temperature is 15°C. The ratio is gypsum: silica sol: water = 100:1:30. After stirring evenly, the mixed slurry is injected into the honeycomb mold, and after 30 minutes, it is molded, demolded, and dried to obtain a gypsum-based honeycomb carrier.

[0081] 2) Mixing the nano-titanium dioxide photocatalyst and water to obtain a titanium dioxide photocatalytic slurry with stirring at a stirring speed of 300 r / min, a stirring time of 5 min, a stirring temperature of 15° C., and a solid content of the titanium dioxide photocatalytic slurry of 10%.

[0082] 3) Immerse the gypsum-based honeycomb ceramic carrier in 1) into the titanium dioxide photocatalytic slurry in 2) to obtain a gypsum-based honeycomb composite photocatalytic plate with a surface-loaded titanium dioxide photocatalyst. The gypsum-based silica sol honeycomb composite photocatalytic plate with a surface-loaded titanium dioxide photocatalyst is placed in an oven for drying, and a gypsum-based silica gel honeycomb composite photocatalytic plate is obtained after drying. The immersion temperature is 35°C, the immersion time is 5s, the drying temperature is 50°C, and the drying time is 12h. This embodiment can obtain a gypsum-based silica gel honeycomb composite photocatalytic plate with a 24h photocatalytic efficiency of 35%.

[0083] By comparing the 24h photocatalytic efficiency of Example 1 with that of Comparative Example 1, it can be seen that the 24h photocatalytic efficiency of Example 1 is much higher than that of Comparative Example 1, which is related to the role of silica sol in bonding titanium dioxide on the gypsum surface. Testing the titanium dioxide content on its surface found that the titanium dioxide content on the surface of the carrier of Example 1 is 1.8 times that of the carrier of Comparative Example 1.

[0084] Example 2

[0085] This embodiment provides a method for preparing a photocatalytic plate, comprising the following steps:

[0086] 1) Mix gypsum, silica sol and water, and stir them with a stirrer to obtain a mixed slurry. The silica sol concentration is 40%, the stirring speed is 300r / min, the stirring time is 3min, and the stirring temperature is 20°C. The ratio is gypsum: silica sol: water = 100:2:35. After stirring evenly, the mixed slurry is injected into the honeycomb mold, and after 30 minutes, it is molded, demolded, and dried to obtain a gypsum-based honeycomb carrier.

[0087] 2) Mixing and stirring the nano-titanium dioxide photocatalyst and water to obtain a titanium dioxide photocatalytic slurry. The stirring speed is 500 r / min, the stirring time is 3 min, the stirring temperature is 30° C., and the solid content of the titanium dioxide photocatalytic slurry is 20%.

[0088] 3) Mix the titanium dioxide photocatalytic slurry and silica sol and stir to obtain a titanium dioxide photocatalytic slurry containing silica sol. Sol concentration 35%, stirring speed 200r / min, stirring time 2min, stirring temperature 25°C

[0089] Ratio: titanium dioxide photocatalytic slurry: silica sol = 50:100

[0090] 4) Immerse the gypsum-based honeycomb ceramic carrier in 1) into the titanium dioxide photocatalytic slurry containing silica sol in 3) to obtain a gypsum-based silica sol honeycomb composite photocatalytic plate with a surface-loaded titanium dioxide photocatalyst. The gypsum-based silica sol honeycomb composite photocatalytic plate with a surface-loaded titanium dioxide photocatalyst is placed in an oven for drying, and a gypsum-based silica gel honeycomb composite photocatalytic plate is obtained after drying. The immersion temperature is 30°C, the immersion time is 20s, the drying temperature is 60°C, and the drying time is 5h. This embodiment can obtain a gypsum-based silica gel honeycomb composite photocatalytic plate with a 24h photocatalytic efficiency of 89%.

[0091] Comparative Example 2

[0092] This comparative example provides a method for preparing a photocatalytic plate, comprising the following steps:

[0093] 1) Mix gypsum and water and stir them with a stirrer to obtain gypsum slurry. The stirring speed is 300r / min, the stirring time is 3min, and the stirring temperature is 20°C. The ratio is gypsum: water = 100:35. After stirring evenly, the gypsum slurry is injected into the honeycomb mold, and after 30 minutes, it is molded, demolded, and dried to obtain a gypsum-based honeycomb carrier.

[0094] 2) Mixing and stirring the nano-titanium dioxide photocatalyst and water to obtain a titanium dioxide photocatalytic slurry. The stirring speed is 500 r / min, the stirring time is 3 min, the stirring temperature is 30° C., and the solid content of the titanium dioxide photocatalytic slurry is 20%.

[0095] 3) Mix the titanium dioxide photocatalytic slurry and silica sol and stir to obtain a titanium dioxide photocatalytic slurry containing silica sol. Sol concentration 35%, stirring speed 200r / min, stirring time 2min, stirring temperature 25°C

[0096] Ratio: titanium dioxide photocatalytic slurry: silica sol = 50:100

[0097] 4) Immerse the gypsum-based honeycomb ceramic carrier in 1) into the titanium dioxide photocatalytic slurry containing silica sol in 3) to obtain a gypsum / silica sol honeycomb composite photocatalytic plate with a surface-loaded titanium dioxide photocatalyst. The gypsum / silica sol honeycomb composite photocatalytic plate with a surface-loaded titanium dioxide photocatalyst is placed in an oven for drying, and a gypsum / silica gel honeycomb composite photocatalytic plate is obtained after drying. The immersion temperature is 30°C, the immersion time is 20s, the drying temperature is 60°C, and the drying time is 5h. This embodiment can obtain a gypsum-based silica gel honeycomb composite photocatalytic plate with a 24h photocatalytic efficiency of 69%.

[0098] By comparing the 24h photocatalytic efficiency of Example 2 with that of Comparative Example 2, it can be seen that the 24h photocatalytic efficiency of Example 2 is higher than that of Comparative Example 1, which is related to the porous structure formed by silica sol inside the gypsum. The specific surface area was tested and it was found that the titanium dioxide content on the surface of the carrier of Example 1 was 1.2 times that of the carrier of Comparative Example 1.

[0099] Example 3

[0100] This embodiment provides a method for preparing a photocatalytic plate, comprising the following steps:

[0101] 1) Mix gypsum, silica sol and water, and stir them with a stirrer to obtain a mixed slurry. The silica sol concentration is 50%, the stirring speed is 1000r / min, the stirring time is 1min, and the stirring temperature is 35°C. The ratio is gypsum: silica sol: water = 100:3:40. After stirring evenly, the mixed slurry is injected into the honeycomb mold, and after 30 minutes, it is molded, demolded, and dried to obtain a gypsum-based honeycomb carrier.

[0102] 2) Mixing and stirring the nano-titanium dioxide photocatalyst and water to obtain a titanium dioxide photocatalytic slurry. The stirring speed is 1000 r / min, the stirring time is 1 min, the stirring temperature is 35° C., and the solid content of the titanium dioxide photocatalytic slurry is 30%.

[0103] 3) Mix the titanium dioxide photocatalyst slurry and silica sol to obtain a titanium dioxide photocatalyst slurry containing silica sol. Sol concentration 50%, stirring speed 300r / min, stirring time 5min, stirring temperature 35°C

[0104] Ratio: Titanium dioxide photocatalytic slurry: silica sol = 100:100

[0105] 4) Immerse the gypsum-based honeycomb ceramic carrier in 1) into the titanium dioxide photocatalytic slurry containing silica sol in 3) to obtain a gypsum-based silica sol honeycomb composite photocatalytic plate with a surface-loaded titanium dioxide photocatalyst. The gypsum-based silica sol honeycomb composite photocatalytic plate with a surface-loaded titanium dioxide photocatalyst is placed in an oven for drying, and a gypsum-based silica gel honeycomb composite photocatalytic plate is obtained after drying. The immersion temperature is 15°C, the immersion time is 60s, the drying temperature is 80°C, and the drying time is 3h. This embodiment can obtain a gypsum-based silica gel honeycomb composite photocatalytic plate with a 24h photocatalytic efficiency of 85%.

[0106] Although preferred embodiments of the present invention have been described, additional changes and modifications may be made to these embodiments by those skilled in the art once the basic inventive concepts are known. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention. Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate, characterized in that: The steps include: S1, preparation of gypsum-based honeycomb carrier based on gypsum and silica sol; S2, preparing titanium dioxide photocatalytic slurry; S3, preparing titanium dioxide photocatalytic slurry containing silica sol; S4, preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate.

2. The method for preparing a gypsum-based silica gel honeycomb composite photocatalytic plate according to claim 1, characterized in that: The S1 includes: S11, mixing gypsum, silica sol and water to obtain a first mixture; S12, stirring the first mixture with a stirrer to obtain a mixed slurry. S13, after stirring evenly, injecting the mixed slurry into a honeycomb mold, and molding, demoulding, and drying after 30 minutes to obtain a gypsum-based honeycomb carrier.

3. The method for preparing a gypsum-based silica gel honeycomb composite photocatalytic plate according to claim 2, characterized in that: The concentration of the silica sol is 30% to 50%, the stirring speed is 100 to 500 r / min; the stirring time is 1 to 5 min; the stirring temperature is 15° C. to 35° C.; the mass ratio of gypsum: silica sol: water is 100:(1-3):(30 to 40).

4. The method for preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate according to claim 3, characterized in that: The S2 includes: S21, mixing the nano titanium dioxide photocatalyst and water to obtain a first mixture; S22, stirring the first mixture to obtain titanium dioxide photocatalytic slurry.

5. The method for preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate according to claim 4, characterized in that: The stirring speed is 300 r / min to 1000 r / min, the stirring time is 1 to 5 min, the stirring temperature is 15° C. to 35° C., and the solid content of the titanium dioxide photocatalytic slurry is 10% to 30%.

6. The method for preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate according to claim 5, characterized in that: The S3 includes: S31, mixing the titanium dioxide photocatalytic slurry and silica sol to obtain a second mixture; wherein the mass ratio of the titanium dioxide photocatalytic slurry: silica sol = (10-100): 100; S32, stirring the second mixture to obtain titanium dioxide photocatalytic slurry containing silica sol.

7. The method for preparing a gypsum-based silica gel honeycomb composite photocatalytic plate according to claim 6, characterized in that: In the titanium dioxide photocatalytic slurry containing silica sol, the concentration of silica sol is 30% to 50%, the stirring speed is 100 r / min to 300 r / min, the stirring time is 1 to 5 min, and the stirring temperature is 15° C. to 35° C.

8. The method for preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate according to claim 7, characterized in that: The S4 includes: S41, using a fixture to immerse the gypsum-based honeycomb carrier into the titanium dioxide photocatalytic slurry containing silica sol for impregnation, to obtain a gypsum-based silica sol honeycomb composite photocatalytic plate with a titanium dioxide photocatalyst loaded on the surface; S42, placing the gypsum-based silica sol honeycomb composite photocatalytic plate with titanium dioxide photocatalyst loaded on the surface in an oven for drying, and obtaining the gypsum-based silica gel honeycomb composite photocatalytic plate after drying.

9. The method for preparing a gypsum-based silicone gel honeycomb composite photocatalytic plate according to claim 8, characterized in that: The immersion temperature is 15° C. to 35° C., and the immersion time is 5s to 60s; the drying temperature is 50° C. to 80° C., and the drying time is 3h to 12h.

10. Application of the preparation method of the gypsum-based silicone gel honeycomb composite photocatalytic plate according to any one of claims 1 to 9 in photocatalytic reactions.